PERAN OPERATOR TELEPON PADA LAYANAN PESAN ANTAR - Nani Nuraini Sarah (Jurnal Sekretari Universitas Pamulang, 2015)
ABSTRAKThe Role of Operators in Delivery Service.(This paper is excerpted from the final project report entitled ‘The Role of Media Communication Especially the use of telephone in PT Fast Food Indonesia Tbk’)As we know, technology offers much ease to mankind, especially in communication. Without exception, these advantages make breakthrough in restaurant business. Delivery service which is as old as the business itself use telephones in delivering the goods to costumersThe aim of this present paper is to show the frame work of delivery service, the flow of communication and the importance of the professionals persons behind its success .Operators, the Back up and the Riders/Home Delivery have to work as a team. As they are the front line that directly deal with customers, they must demonstrate their professionalism, such as courtesy, on time delivery and making sure that customers are happy their ordering experience.Data for this report was collected from PT Fast Food Indonesia, tbk in BSD square by a student who was directly involved in working as an operator for 3 (three) months. Her experience as an operator had brought her to a better understanding of the whole system of delivery service. With the support from  her supervisor and her colleagues in the restaurant, she managed to get through her exhausted working time. After her valuable and interesting experience,  she decided to share it in a report. The report shows that not only the technology component should be provided but the man power should also be trained for exceptional performance.